ANALISIS RASIO LIKUIDITAS DAN RASIO PROFITABILITAS (STUDI PERUSAHAAN FARMASI YANG TERDAFTAR PADA BURSA EFEK INDONESIA - Melisa A Putri (Majalah Ilmiah Manajemen STIE Aprin Palembang, 2021)
The purpose of this study was to determine the level of liquidity ratios and profitability ratios of pharmaceutical companies listed on the Indonesia Stock Exchange. This study uses quantitative data, namely the financial statements of pharmaceutical companies listed on the IDX from 2018-2020. Data collection techniques in the research are in the form of documentation and observation of financial statements and data analysis using descriptive analysis. The results showed that the liquidity ratios of Kalbe Farma, Tbk and PT Industri Jamu dan Farmasi Sido Muncul, Tbk could be said to be good. This can be seen from the dimensions of the liquidity ratio, namely the current ratio, quick ratio and cash ratio of the company which exceeds the value of the company's current liabilities. However, for several other companies such as Darya Varia Laboratoria, Tbk, Indofarma, Tbk, Kimia Farma, Tbk, Merck, Tbk, PT Phapros, Tbk, Pyridam Farma, Tbk, and Tempo Scan Pasifik, Tbk, it is necessary to re-evaluate related to current assets available to guarantee each of the company's current liabilities. The profitability ratio of PT Industri Jamu dan Farmasi Sido Muncul, Tbk can be said to be good. This can be seen from the dimensions of the profitability ratios, namely profit margin on sales, basic earning power, return on assets and high return on equity so that it shows the company's ability to generate profits. However, for some other pharmaceutical companies, it is necessary to re-evaluate related to costs, assets and equity owned by the company so that they can be managed effectively.